Application of a catalyst-free Domino Mannich/Friedel-Crafts alkylation reaction for the synthesis of novel tetrahydroquinolines of potential antitumor activity. Issue 9 (1st March 2018) - Castillo, Juan-Carlos; Jiménez, Elizabeth; Portilla, Jaime; Insuasty, Braulio; Quiroga, Jairo; Moreno-Fuquen, Rodolfo; Kennedy, Alan R.; Abonia, Rodrigo
Abstract: A useful and efficient method to construct diversely substituted 1, 2, 3, 4-tetrahydroquinolines in good to excellent yields has been developed through a catalyst-free Domino Mannich and intramolecular Friedel-Crafts alkylation reactions of N -arylamines with paraformaldehyde and electron-rich olefins via the formation of N -aryl- N -alkylmethyleneiminium ions as the key intermediates to afford the target products. Nine of the new compounds were evaluated in the US National Cancer Institute (NCI), where compound 5f (R1 = 6-MeO, R2 =  p -ClC6H4 and X = pyrrolidin-2-onyl) presented a remarkable activity against 57 cancer cell lines, with the most important GI50 values ranging from 1.46 to 8.28 μM from in vitro assays. Further studies performed over the active compound 5f on HCT116 colon cancer cells indicated that its effect on cell death is exerted through a cell cycle arrest (S phase) in a dose dependent manner, as well as suppression on the cell proliferation process. Graphical abstract: